Athlete’s health maintanance management during a pandemic Covid-19: A case study at a National Sport Hospital - Bunga Listia Paramita; Dumilah Ayuningtyas (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
Coronavirus disease 2019 (Covid-19) pandemic and Large-Scale Social Restriction (PSBB) policy in Indonesia caused health problems for athletes, such as mental, psychological, nutritional, decreased maximum oxygen consumption (VO2Max), loss of strength and muscle mass. Athletes are also individuals who are at risk of being infected Covid-19 so they need health care services. This effort is being realized by the National Sports Hospital (RSON). This study aims to explain the athlete's health maintenance activities by RSON during the Covid-19 pandemic, to analyze the possible gaps, and how to overcome them. This research uses descriptive method and case stnudy approach based on the experience of researchers as RSON medical staff and secondary data from March 1, 2020 to July 31, 2020 starting from the preparation stage with system approach (man, money, material, method, machine), implementation stage (promotive, preventive, curative, and rehabilitative), and output. The entire data was then analyzed based on literature. The results showed that RSON was able to make preparations that support athlete health care, such as socialization and screening for covid-19, treatment and rehabilitation of athletes both directly and online media. Some conditions that still have gaps such as the lack of athletes being screened, and not yet doing routine monitoring of athlete's health during the self training period can be overcome by resocialization and starting routine monitoring activities. Activities such as monitoring the athlete's diet, increasing the role in the prevention of covid-19 in disabled athletes, and collaboration with trainers and team management in the